2008
DOI: 10.1002/jmri.21418
|View full text |Cite
|
Sign up to set email alerts
|

Change in knee cartilage T2 in response to mechanical loading

Abstract: Purpose: To assess the clinical feasibility of magnetic resonance (MR) imaging with a mechanical loading system for evaluation of load-bearing function in knee joints using cartilage T2 as a surrogate of cartilage matrix changes. Materials and Methods:Sagittal T2 maps of the medial and lateral femorotibial joints of 22 healthy volunteers were obtained using 3.0T MR imaging. After preloading for 6 -9 minutes, MR images under static loading conditions were obtained by applying axial compression force of 50% of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
104
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(114 citation statements)
references
References 26 publications
9
104
1
Order By: Relevance
“…CBCT equipped with flat panels is advantageous over conventional CT in that it has high spatial resolution (e.g., 150 μm isotropic for flat-panel angiographic CT). Considering cartilage contact area 45 and thickness 46,47 changes on the order of submillimeter as loads were applied, conventional CT could lead to inaccurate measurements of soft tissue structures and alignment of the bones (e.g., patella, femur, and tibia) in knee. Thus, flat panel CBCT could extract useful information of the knee joint under loading conditions which was not currently achievable.…”
Section: Discussionmentioning
confidence: 99%
“…CBCT equipped with flat panels is advantageous over conventional CT in that it has high spatial resolution (e.g., 150 μm isotropic for flat-panel angiographic CT). Considering cartilage contact area 45 and thickness 46,47 changes on the order of submillimeter as loads were applied, conventional CT could lead to inaccurate measurements of soft tissue structures and alignment of the bones (e.g., patella, femur, and tibia) in knee. Thus, flat panel CBCT could extract useful information of the knee joint under loading conditions which was not currently achievable.…”
Section: Discussionmentioning
confidence: 99%
“…Smaller T2 decrease was observed in the intermediate cartilage layer, and no change was observed in the deep cartilage layer. Nishii et al reported similar results with a mechanical loading system [46]. T2 maps were acquired from 22 healthy volunteers under static loading conditions by applying axial compression force of 50% of body weight during imaging.…”
Section: Association Of T2 Measurements With Physical Activitymentioning
confidence: 93%
“…Significantly elevated T2 values were reported after 30 min of unloading the knee due to decompression of the cartilage and consequently increasing cartilage water content [45]. Loading and unloading the knee joint considerably affect the T2 values [46]. Therefore, physical activity before the scan and the time point of the T2 sequence within the MR protocol are important.…”
mentioning
confidence: 98%
“…Thanks to the calculation and the display of the T2 maps it is possible to detect the changes in the collagen component of the ECM noninvasive and more precisely to detect the changes in the water content (distribution of interstitial water in the solid matrix) which are not normally visible in conventional MRI images (Nishii et al, 2008;Welsch et al, 2008).…”
Section: T2 Relaxation In Cartilage and Meniscimentioning
confidence: 99%